A Novel CVD Growth of g‐C3N4 Ultrathin Film on NiCo2O4 Nanoneedles/Carbon Cloth as Integrated Electrodes for Supercapacitors. Issue 22 (14th September 2018) - Guo, Wen; Ming, Shujun; Chen, Zhen; Bi, Jiajun; Ma, Yajuan; Wang, Jingyu; Li, Tao
Abstract: Although g‐C3 N4 possesses many features such as a graphene‐like 2D π‐conjugated planar layered structure, high nitrogen content, excellent mechanical strength and flexibility, as well as high thermal and chemical stability, there are only a few studies on the exploration of g‐C3 N4 as active materials for supercapacitors. This could be largely attributed to the fact that the above advantages of g‐C3 N4 to hybrid with other materials are still not fully established. Herein, we successfully develop a facile low‐temperature CVD method to grow g‐C3 N4 ultrathin films with several nanometers thickness on the surface of NiCo2 O4 nanoneedles. Subsequently, a NiCo2 O4 nanoneedles@g‐C3 N4 ultrathin film core‐shell nanostructures/carbon cloth (NiCo2 O4 NNs@g‐C3 N4 /CC) integrated electrode was obtained. Thanks to the ultrathin film, a core‐shell nanostructure, as well as intrinsic features of g‐C3 N4, the as‐obtained integrated electrode displays excellent electrochemical performance, exhibiting an areal capacitance of 2.83 F cm −2 as well as high cycling stability (5.88 % loss after 10 000 cycles). Our results clearly demonstrate that the g‐C3 N4 ultrathin film obtained through this facile CVD method developed has potential in hybridizing with other transition metal oxides as electrode materials for supercapacitors and, more importantly, this convenient synthesis method may also be widely used for other applications such as designing new heterojunction photocatalysts. Abstract : Stable progress : A g‐C3 N4 ultrathin film coated on NiCo2 O4 nanoneedle arrays/carbon cloth is achieved by using a novel CVD method. This is then used as a binder‐free electrode for supercapacitors. Electrochemical tests show that the coating of the g‐C3 N4 ultrathin film could significantly enhance the areal capacitance and stability of the electrode.